2011
DOI: 10.1371/journal.pone.0018801
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Based Tumor Vaccination in Prostate and Renal Cell Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundMore than 200 clinical trials have been performed using dendritic cells (DC) as cellular adjuvants in cancer. Yet the key question whether there is a link between immune and clinical response remains unanswered. Prostate and renal cell cancer (RCC) have been extensively studied for DC-based immunotherapeutic interventions and were therefore chosen to address the above question by means of a systematic review and meta-analysis.Methodology/Principal FindingsData was obtained after a systematic literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 80 publications
3
150
0
7
Order By: Relevance
“…Side effects seen with the majority of DC vaccination protocols were minimal and selflimiting, mainly including flu-like symptoms, fever, and local reactions at the injection site. Grade 3 or 4 treatment-related toxicity is extremely uncommon when DC vaccination is given as monotherapy (15). These data are confirmed by the available data from phase III trials where DC vaccination is compared with placebo (16)(17)(18)(19).…”
Section: Safetymentioning
confidence: 68%
See 1 more Smart Citation
“…Side effects seen with the majority of DC vaccination protocols were minimal and selflimiting, mainly including flu-like symptoms, fever, and local reactions at the injection site. Grade 3 or 4 treatment-related toxicity is extremely uncommon when DC vaccination is given as monotherapy (15). These data are confirmed by the available data from phase III trials where DC vaccination is compared with placebo (16)(17)(18)(19).…”
Section: Safetymentioning
confidence: 68%
“…Later trials demonstrated superiority of mature DCs over their immature counterparts in terms of the immunogenicity and clinical outcome (15,(20)(21)(22). Besides their enhanced migratory capacity (23), mature DCs also have a higher expression of MHC and costimulatory molecules.…”
Section: Maturation Of Dcsmentioning
confidence: 99%
“…Clinical responses to vaccine were evaluated according to the World Health Organization criteria (18): complete response was defined as complete disappearance of tumor, partial response was defined as ≥50% reduction in the product of two longest perpendicular diameters of tumor without the appearance of new metastases, stable disease was defined as <50% decrease to <25% increase in tumor size, and progressive disease was defined as ≥25% increase in tumor size or the appearance of new metastases. Among the 166 patients who finished therapy, 77 (46%) had clinical response with 6 complete responses, 13 partial responses, and 58 disease stabilizations (17). Treatment with dendritic cell-based vaccine was only accompanied by mild adverse effects such as local reactions at the injection site, flu-like symptoms, and fever.…”
Section: Introductionmentioning
confidence: 99%
“…44 Another promising new approach is adoptive cell therapy using engineered T-cell Chimeric Antigen Receptor (CAR). 45 Clinical trial results for therapeutic RCC vaccines We reviewed 6 clinical trials of RCC-specific therapeutic vaccines administered in an adjuvant or a metastatic setting: three completed phase III trials (Reniale, [46][47] Trovax, [48][49][50] and Vitespen 51 ) and three phase II trials (TG4010, 52 AGS003, [53][54] and IMA901 21 ), as well as a meta-analysis of dendritic cell (DC)-based vaccines in mRCC 55 ( Table 1). The publications were retrieved from a Medline search (from january 2004 to november 2014).…”
Section: Immune Escape Mechanisms In Ccrccmentioning
confidence: 99%
“…The cellular immune response and DC dose (mean= 38.7£10*6 cells) were the main predictors of response. 55 …”
Section: Dc-vaccinesmentioning
confidence: 99%